Long-Term Supplier Selection Problem: A Case Study - Senyigit, Ercan; Soylemez, Ismet; Atici, Ugur (Sciencepark Sci, Organization & Counseling Ltd, 2017)
The problem to select a supplier has taken the best supplier according to all combinations of sorting criteria. With regard to the supplier selection problem, the priority ranking of the criteria taken into consideration to solve this problem has a direct impact on the determination of the "optimum" supplier. This paper provides a case study made for the supplier selection problem involving all possible rankings in cable transfer pulleys used in rolling products by a company X which is active in a steel cable industry in Kayseri, Turkey. NG's model is used in the solution stage in the application. In this research, a new type of supplier selection problem called long-term supplier selection problem with a case study is proposed. Finally, solution of long-term supplier selection problem by a new approach is presented. According to the values obtained by scoring, it has been determined that a long-term agreement can be concluded with the supplier no. 4 (S4) and a long or medium-term agreement can be made with supplier no. 2 (S2). S1, S3 and S5 are determined as the suppliers with the worst performances. As a result, it has been shown to the company that working with S1, S3 and S5 suppliers will not generate any benefits.
Keywords: Supply Chain Management; Supplier Development; Multi-Criteria Supplier Selection; Long-Term Supplier Selection Problem; Case Study